Loyalitas Nasabah dari Citra Merek dan Kepercayaan Merek Bank Syariah Indonesia cabang Jombang - Fahimah, Mar'atul; Rahman, Muhammad Taufiqur (JoEMS (Journal of Education and Management Studies), 2023)
This study aims to analyze the influence of brand image and brand trust on customer loyalty at the Jombang branch of the Indonesian Sharia Bank. The influence of brand image and brand trust on customer loyalty is an important topic in the Islamic banking industry, especially to understand the factors that can influence customers in choosing and remaining loyal to use certain bank services. The research method used was a survey with questionnaires distributed to 100 customer respondents of the Jombang branch of Bank Syariah Indonesia. The data obtained were analyzed using regression analysis to examine the relationship between brand image, brand trust, and customer loyalty variables. The results of the study show that brand image has a significant positive effect on customer loyalty at the Jombang branch of the Indonesian Sharia Bank. In other words, the customer's positive perception of the bank's brand image can influence the customer's tendency to continue using the bank's services. In addition, brand trustalso has a significant positive effect on customer loyalty. Customer trust in this bank in terms of reliability, sharia compliance and security can strengthen customer loyalty. This research makes an important contribution to the Jombang branch of Bank Syariah Indonesia in understanding the factors that can influence customer loyalty. In developing marketing and brand management strategies, banks need to pay attention to the importance of building a positive brand image and increasing customer trust through consistent reliability, sharia compliance and security. By strengthening brand image and brand trust, banks can increase customer loyalty levels and maintain a strong market share.